Investigations in the modelling and control of a medium voltage hybrid inverter system that uses a low voltage /low power rated auxiliary current source inverter - Papadopoulos, Savvas; Rashed, Mohamed; Klumpner, Christian; Wheeler, Patrick (IEEE, 2016)
Hybrid converters consist of a main inverter processing the bulk of the power with poor waveform performance and a fast and versatile auxiliary inverter to correct the distortion. In this paper, the main converter is a medium voltage NPC inverter and the auxiliary inverter is a low-voltage and low-current rated current source inverter (CSI), with series capacitor being used to minimize the CSI voltage stress. The result is a high output current quality which is obtained with a very low switching stress in the main converter and a very small added installed power (<4%) in the CSI. This paper expands this concept by investigating the hybridization of a medium voltage inverter with an existing LCL filter and investigates the additional challenges related to resonances and proposes a solution for stable operation. Experimental validation of active ripple cancellation has been provided at 3kW.